Winning body language : control the conversation, command attention, and convey the right message--without saying a word - Bowden, Mark, 1951- (McGraw-Hill, 2010)
The Unique System of Nonverbal Skills Used by the Most Effective Leaders in Business Today CONTROL THE CONVERSATION, COMMAND ATTENTION, AND CONVEY THE RIGHT MESSAGE--WITHOUT SAYING A WORD Whether you're presenting an idea, delivering a speech, managing a team, or negotiating a deal, your body language plays a key role in your overall success. This ingenious step-by-step guide, written by an elite trainer of Fortune 50 CEOs and G8 world leaders, unlocks the secrets of nonverbal communication--using a proven system of universal techniques that can give you the ultimate professional advantage. Learn easily how to: Successfully master the visual TruthPlane around you to win trust now. Gesture in a way that gains everyone's attention- even before you speak. Appeal to others' deep psychological needs for immediate rapport and influence. You'll discover how to sit, stand, and subtly alter your body language to move with confidence, control conversations, command attention, persuade and influence others, and convey positive energy-without saying a word. It's the one key to success nobody talks about!